An empirical investigation on the temporal variations of urban heat island in greater Kuala Lumpur / Logaraj Ramakreshnan - Logaraj , Ramakreshnan (2022)
Background: Greater Kuala Lumpur (GKL) suffered inevitable territorial urban development with many primary urban areas within the conurbation experiencing the Urban Heat Island (UHI) phenomenon, expressed as the temperature difference between areas of different degrees of urbanization process. Nonetheless, very limited studies have evaluated nor understood the temporal dynamics of canopy-level UHI in the local context. Aim: This study investigated the temporal variations of canopy-level UHI in selected urban stations, Petaling Jaya (PJ) and Subang (SUB), of GKL in relation to the reference Sepang (SEP) suburban station. This study also investigated the association between selected meteorological variables (relative humidity and wind speed) and UHI Intensity (UHII) in the urban stations. Methods: Hourly dataset of 112 calm and clear days of the year 2016 corresponding to all the monsoon seasons obtained from the meteorological observatories are included in the analysis after excluding the synoptic scale effects. The mean differences between the selected meteorological variables (relative humidity and wind speed) of the urban and suburban stations are tested using one-way ANOVA and Tukey’s HSD test. Thereafter, the association between the meteorological variables and UHII is evaluated using Pearson correlation and Multivariate Linear Regression models. Results: The difference between the means of the average temperature of PJ-SEP pair is statistically significant during the northeast (Q = 4.037, p < 0.05) and southwest monsoon (Q = 11.344, p < 0.001) seasons whereas the SUB-SEP pair registers statistical significance during the southwest monsoon (Q = 7.742, p < 0.001) only. The yearly average of the UHII in the PJ station (1.25 °C) is higher compared to the SUB station (0.67 °C). High UHII of 0.74 - 1.70 °C is recorded in the PJ station compared to the SUB (0.15 - 1.40 °C) station during relatively drier months associated with the southwest monsoon seasons. In terms of diurnal variations, the daily average of UHII in the PJ station (1.19 °C) is higher compared to the SUB (0.73 °C) station, with the magnitudes surpassing the daily average recorded before sunrise and from late afternoon until the midnight. In addition, the highest cooling rate in SUB (1.10 °C/h) and PJ (0.90 °C/h) is attained around 6 p.m. In contrast, the cooling rate of SEP station is the lowest before sunrise (0.15 – 0.34 °C/h) and after sunset (0.20 – 0.47 °C/h), justifying the development of nocturnal UHI with high intensities in these urban stations. Indeed, most of the hourly UHIIs between 1-3 °C occur at night during all the monsoon seasons. Besides, the relative humidity demonstrated a moderate negative linear relationship with UHII in PJ (r = -0.568, p < 0.001) and SUB (r = -0.629, p < 0.001) stations. Likewise, hourly change in UHII (ΔUHII) and relative humidity (ΔRH) also revealed a moderate negative correlation in PJ (r = -0.508, p < 0.001) and SUB (r = -0.543, p < 0.001) stations. On the other hand, wind speed exerts a low and moderate negative correlation with UHII in the PJ (r = -0.450, p < 0.001) and SUB (r = -0.601, p < 0.001) stations. In terms of hourly changes, a moderate negative relationship (r = -0.588, p < 0.001) is observed between ΔUHII and wind speed (ΔWS) in the SUB station. Nonetheless, this effect is insignificant (r = -0.147, p = 0.087) in the PJ station. The combined influences of relative humidity and wind speed on UHII indicating a strong and moderate negative relationship in PJ (r = -0.714, p < 0.001) and SUB (r = -0.630, p < 0.001) stations, respectively. Conclusion: The findings of this study is expected to fill the existing knowledge gap on the magnitudes of UHII of urban stations in GKL and how strongly the meteorological factors can affect the UHII in an equatorial country like Malaysia by adding more research evidence from the tropical region.